Targeting market segment needs with public-good crop breeding investments: A case study with potato and sweetpotato focused on poverty alleviation, nutrition and gender - Ojwang, Sylvester Okoth; Okello, Julius Juma; Otieno, David Jakinda; Mutiso, Janet Mwende; Lindqvist-Kreuze, Hannele; Coaldrake, Peter; Mendes, Thiago; Andrade, Maria; Sharma, Neeraj; Gruneberg, Wolfgang; Makunde, Godwill; Ssali, Reuben; et al. (Frontiers in Plant Science, 2023)
Crop breeding programs have often focused on the release of new varieties that target yield improvement to achieve food security and reduce poverty. While continued investments in this objective are justified, there is a need for breeding programs to be increasingly more demand-driven and responsive to the changing customer preferences and population dynamics. This paper analyses the responsiveness of global potato and sweetpotato breeding programs pursued by the International Potato Center (CIP) and its partners to three major development indicators: poverty, malnutrition and gender. Our analysis reveals that future investments in breeding programs will achieve greater impacts by developing varieties for market segments and pipelines that have more poor rural people, high stunting rates among children, anemia prevalence among women of reproductive age, and where there is high vitamin A deficiency. In addition, breeding strategies that reduce gender inequality and enhance appropriate change of gender roles (hence gender transformative) are also required.